Pachydermoperiostosis ('Touraine-Solente-Gole' Syndrome) - R Sharma; S Pandey; D Choudhary; DB Pokhrel (Nepal Journal of Dermatology, Venereology & Leprology)
DOI: http://dx.doi.org/10.3126/njdvl.v11i1.7937